The Meadow-Brook girls under canvas, or, Fun and frolic in the summer camp - Aldridge, Janet. (Fun and frolic in the summer camp., 1913)
Girls go off to summer camp together for some fun and frolic and encounter a mystery along the way.
8 p. of publisher's catalog follows text.
Girls go off to summer camp together for some fun and frolic and encounter a mystery along the way.
Keywords: Hazing / Juvenile fiction.; Ghost stories. / http://id.loc.gov/authorities/subjects/sh85054811; Girls / Conduct of life / Juvenile fiction.; Friendship / Juvenile fiction. / http://id.loc.gov/authorities/subjects/sh2008103472; Camping / Juvenile fiction.